Thinking of the Chilean Right, 1925-1932 - Pinto-Vallejos, J (Ltd "Integration: Education and Science", 2020)
This article explores the rise of Chile s "Old Right" between 1925 and 1931, especially the economic-entrepreneurial Right and the political Right clustered around the traditional Conservative and Liberal parties. Our hypothesis holds that more than one Right arose during these years, sharing some basic traits but with different derivations: One associated with military President Ibáñez, with strong programmatic influence but no party expression; and another linked to business and traditional politics. These crystallized into the "old" Right: Parties and business associations sharing a bellicose political style, ample social alliances, and well-defined programmatic aims (quite distant from the pragmatic flexibility often ascribed to them). In formulating this platform, the influence of the economic Right proved decisive, stamping its imprint for the remainder of the 20th century. © 2020 Ltd "Integration: Education and Science". All rights reserved.
Keywords: Right-wing parties; entrepreneurs; conservatism; liberalism; State; Chile